A Comparative Exploration of the Motivational Factors of Faith-Based and Secular NGOs and Their Actors in Cambodia. Issue 9 (3rd July 2020) - Frame, John
ABSTRACT: Secular and faith-based NGOs are significant non-state service providers in the developing world, yet limited research has been conducted comparing their motivational factors. This paper considers the motivations driving the work of Christian faith-based organisations (FBOs) and secular NGOs working with women and children in Cambodia. The qualitative research design included 41 interviews, with respondents from thirteen FBOs and twelve secular NGOs. The paper makes two substantive arguments. First, faith-related motivations were expressions of the ways in which religious faith infused FBOs in the study. Second, the development context in which the organisations worked led to a clear distinction between FBOs and secular NGOs. The paper makes a theoretical contribution about the importance of considering the convergence of both the development context and the infusion of faith in FBOs when examining similarities and differences between these two types of organisations.